Trends in Prescription Drug Spending Leading Up to Health Reform. (August 2014) - Blavin, Fredric; Waidmann, Timothy; Blumberg, Linda J.; Roth, Jeremy
Over the past decade, prescription drug expenditures grew faster than any other service category and comprised an increasing share of per capita health spending. Using the 2005 and 2009 Medical Expenditure Panel Surveys, this analysis identifies the sources of spending growth for prescription drugs among the nonelderly population. We find that prescription drug expenditures among the nonelderly increased by 14.9 billion (9.2%) from 2005 to 2009 and expenditures increased in 12 out of the 16 therapeutic classes. Changes in the number of users and expenditures per fill were the drivers of spending fluctuations in these categories. The main results also provide insight into generic entry, the price gap between brand and generic drugs, and from a health reform evaluation perspective, the importance of separating prepolicy secular trends in expenditures from changes attributable to specific forces, such as shifts toward generic versions of blockbuster drugs.